PERANCANGAN MEJA RESEPSIONIS BERBASIS MATERIAL MARMER ONYX SEBAGAI ELEMEN ESTETIKA DAN IDENTITAS VISUAL INTERIOR - Annica Etenia; Eva Artmey Mangedaby; Eka Anjani Sapitri (CV. Denasya Smart Publisher, 2026)
A reception desk design plays a crucial role in shaping the first impression and visual identity of an interior space. This study aims to design an onyx marble reception desk that serves both functional and aesthetic purposes in a modern interior. Onyx marble was selected for its translucent characteristics and its capacity to produce distinctive visual effects when combined with lighting, thereby creating an elegant and exclusive ambiance. This study employs a qualitative design approach encompassing stages of needs identification, material study, form exploration, and design development. Analysis was conducted on the interrelationship between material, structure, and lighting to produce a harmonious design aligned with modern commercial interior concepts. The design outcomes demonstrate that the application of onyx marble in the reception desk effectively reinforces the visual identity of the space while significantly enhancing its aesthetic value. Furthermore, this design has the potential to serve as a focal point within the reception area and to support the formation of a professional and characterful spatial image